The Effect of the Guided Inquiry Learning Model on Learning Outcomes and Creative Thinking Skills of High School Students - Ramadhan, Haryo Bagus Wahyu; Astutik, Sri; Nurdin, Elan Artono; Apriyanto, Bejo; Pangastuti, Era Iswara (Universitas Lambung Mangkurat, 2024)
Classroom learning requires the use of effective learning models to support student learning outcomes and creative thinking skills. The Guided Inquiry learning model can be used in class as an alternative learning model. This study aims to examine the effect of the Guided Inquiry model on learning outcomes and creative thinking skills of high school students. The research method used was a Quasi Experimental Design and was designed with a pre-test post-test control group design. Data on learning outcomes were taken using multiple choice of 10 questions and data on creative thinking skills were taken using a description of 5 questions. The research was conducted in class X-7 and X-8 which were selected through cluster random sampling using a lottery technique. The results showed that the learning outcomes and creative thinking skills of the experimental class students were higher than those in the control class. The results of the analysis show that (1) there is a significant effect of the use of the Guided Inquiry learning model on high school student learning outcomes, (2) there is a significant effect of the use of the Guided Inquiry learning model on students' creative thinking skills.